Analisis Hukum Terhadap Anak Sebagai Korban Tindak Pidana Perdagangan Orang - Jogi Septian Bangun Panjaitan; Marlina Marlina; Rizkan Zulyadi (Mahesa Research Center, 2021)
Point of this study is as follows: (a) What are the legal rules for the protection of children as victims of trafficking in persons, (b) What are the factors causing the crime of trafficking in women and children in North Sumatra, (c) What are the policies carried out by the women's empowerment office? and children in North Sumatra in preventing and overcoming traffickers against children. The type of research in this writing is normative legal research. Normative or doctrinal legal research, namely legal research that uses secondary data source research. The results of the research and discussion in this study are: The Legal Rules for the Protection of Children as Victims of Trafficking in Persons are as follows: (a) Law Number 23 of 2002 concerning Child Protection; (b) Law of the Republic of Indonesia Number 21 of 2007 concerning Eradication of the Crime of Trafficking in Persons; (c) Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection; (d) North Sumatra Province Regional Regulation Number 3 of 2014 concerning the Implementation of Child Protection. Factors Causing the Crime of Trafficking in Women and Children in North Sumatra: Several factors that cause child trafficking include the following: (a) Poverty; (b) Low Education Level; (c) Victims of Parental Divorce; (d) Early Sexual Experience; (e) Job Seekers. Policies in overcoming criminal acts of protecting people are carried out in three ways, namely: (a) Primary Prevention, (b) Secondary Prevention, (c) Tertiary Prevention.